Industry Payments to Foot and Ankle Surgeons and Their Effect on Total Ankle Arthroplasty Outcomes. Issue 1 (January 2022) - Safavi, Kiya Shazadeh; Rezvani, Aryan; Healy, Nicholas; Jupiter, Daniel; Panchbhavi, Vinod K.; Janney, Cory
Category: Ankle; Other Introduction/Purpose: The Centers for Medicare & Medicaid Services (CMS) Open Payments public (OPP) database provides a means for increased transparency of physicians' financial relationships with industry. Total ankle arthroplasty is a procedure with long term clinical implications and variable outcomes published in the existing literature. We compared physician-reported conflict-of-interest (COI) disclosures in Foot and Ankle International (FAI) with CMS database information to evaluate for discrepancies. Methods: Articles published in FAI reporting clinical outcomes of total ankle arthroplasty from 2015 and 2019 were reviewed. Payment information in the CMS database was cross-referenced with disclosure statements and International Committee of Medical Journal Editors (ICMJE) forms associated with the manuscript. Statistical analysis was performed to determine if industry payments were appropriately disclosed or influenced outcomes. Results: We reviewed 173 articles pertaining to ankle arthroplasty with 27 meeting inclusion criteria. Of 120 total authors with 98 unique authors, 114 (95%) disclosed appropriately in disclosure statements. Twenty-two papers (82%) had appropriate declarations for the entire manuscript. For the 27 senior authorships, only two discrepancies between manuscript disclosure and the OPP database were noted, showing 13 total disclosures in the OPP database vs 11 disclosed in the manuscript. We found there was no relationship between industry payment and the outcome of the manuscript (P =.725). Conclusion: The majority of author disclosure statements accurately reflected the OPP data. Additionally, payments were not significantly associated with positive outcomes reported for the specific implant. Overall, authors publishing on ankle arthroplasty in FAI are disclosing appropriately per our review.